2014
DOI: 10.1111/jmp.12137
|View full text |Cite
|
Sign up to set email alerts
|

A novel real‐time CTL assay to measure designer T‐cell function against HIV Env+ cells

Abstract: Background To increase the immunosurveillance in HIV infection, we used retroviral vectors expressing CD4-chimeric antigen receptors (CARs) to genetically modify autologous T cells and redirect CTL towards HIV. The CD4 extracellular domain targets Envelope and the intracellular signaling domains activate T cells. The maC46 fusion inhibitor binds HIV and blocks viral replication. Methods We stimulated rhesus PBMCs with αCD3αCD28 and co-transduced T cells with CD4-CAR and maC46 vectors. CD4-CAR transduced T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…We found that the newly designed CAR-T cells, here referred to as VC-CAR-T cells, were able to induce T cell-mediated cytolysis after coculture with gp120-expressing cells and wild-type HIV-1-infected CD4 ϩ T cells. We also found that VC-CAR-T cells display superior potency compared to the CD4-CAR described previously (26,27,(31)(32)(33)(34)(35)(36). Importantly, we have also confirmed that they can effectively kill the reactivated HIV-1-infected CD4 ϩ T lymphocytes isolated from HIV-1-infected patients.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…We found that the newly designed CAR-T cells, here referred to as VC-CAR-T cells, were able to induce T cell-mediated cytolysis after coculture with gp120-expressing cells and wild-type HIV-1-infected CD4 ϩ T cells. We also found that VC-CAR-T cells display superior potency compared to the CD4-CAR described previously (26,27,(31)(32)(33)(34)(35)(36). Importantly, we have also confirmed that they can effectively kill the reactivated HIV-1-infected CD4 ϩ T lymphocytes isolated from HIV-1-infected patients.…”
supporting
confidence: 84%
“…Therefore, we chose to use VRC01-28BBZ-3-expressing T cells, here referred to as VC-CAR-T cells, for subsequent experiments. Previous studies have reported that CD4-based CAR-T cells, referred to here as CD4-CAR-T cells, display direct cytotoxic activity against HIV-1 Env-expressing target cells (26,27,(31)(32)(33)(34)(35)(36). To compare the efficiency of CD4-CAR and VC-CAR, we generated the former by replacing the VC-CAR scFv with the human CD4 extracellular domain and transduced this construct into CD8 ϩ T lymphocytes (Fig.…”
Section: Selection Of the Most Efficient Car Moiety To Identify The mentioning
confidence: 99%
See 1 more Smart Citation
“…Early clinical successes with CARs against leukemia and lymphoma (28,29) have garnered particular recognition (30), and the strategy has been proposed for use against viruses, including HIV (reviewed in references 31, 32, 33, and 34). Indeed, previous reports demonstrated favorable in vitro results with CARs targeted by single-chain variable-region antibody (Ab) constructs directed against the gp120 or gp41 subunits of HIV-1 Env (35)(36)(37)(38) as well as with CARs employing extracellular CD4 domains (35,36,(39)(40)(41)(42). Clinical studies were conducted more than a decade ago with CD4 CARs (43)(44)(45); see also https://clinicaltrials.gov/ct2/show/NCT01013415), and subsequent analyses of peripheral blood samples verified long-term persistence as well as retention of CAR expression and the proliferative potential of adoptively transferred CAR-transduced T cells (CAR-T) (46).…”
mentioning
confidence: 99%
“…[71][72][73][74][75][76][77][78][79][80] used measure of the viable HIV reservoir) and rectal HIV DNA (-0.5 log), and a trend toward less viral rebound, although no decrease in peripheral blood HIV DNA or rectal HIV RNA. 81 Long-term follow-up suggests that this approach was safe and results in long-lived cells with CAR DNA that persisted for more than a decade.…”
Section: Previous Trials Of Anti-hiv Carmentioning
confidence: 99%